Pentahelix Strategy Improving the Performance of MSMEs Malang City (Study on Food and Beverage Sector) - Shelativa Widuroyekti; Ratna Nikin Hardati; Khoiriyah Trianti (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2025)
In Malang City, MSMEs play a significant role in the economy, particularly in the fast-growing food and beverage industry. The goal of this research is to evaluate how food and beverage businesses in Malang City can improve their performance by collaborating with academics, communities, the government, entrepreneurs, and social media. This study utilizes a combination of research methods with a focus on explaining the results in a step-by-step manner. The target population for this research consists of 5,365 food and beverage small and medium enterprises in Malang City, with a sample of 100 participants chosen randomly for the study. Quantitative information was gathered via surveys, whereas qualitative data was obtained through in-depth discussions with various experts. Findings indicate that the academic, community, business, and social media sectors have a noteworthy impact on the success of MSMEs in Malang City, while the government's role is deemed less significant, although this conclusion is supported by insights from the experts. The collaboration between these five sectors enhances the abilities of MSMEs through training, guidance, and marketing support, aiding them in addressing market challenges and enhancing their performance in Malang City. This partnership is anticipated to fortify the MSME industry as the cornerstone of the local economy, boosting job opportunities and reducing unemployment levels.